Constructing Female Education and Empowerment in No Better Time: A Critical Discourse Analysis of Gendered Power Dynamics - Anggita Bella Afrilla Nasution; T. Silvana Sinar; Rahmadsyah Rangkuti; T. Thyra Zein; Alemina Br. Perangin Angin (Universitas PGRI Yogyakarta, 2026)
This study examines the construction of women's education and empowerment in the novel No Better Time through the analysis of feminist critical discourse with Fairclough’s three-dimensional model. The aim of the study was to analyze how educational discourse is constructed as a site of resistance and agency for African American women in the face of gender- and race-based intersectional oppression. The research method uses an interpretive qualitative approach, with data in the form of discursive episodes that represent access to knowledge, formal and informal learning, and agency actions. The analysis was carried out at three levels: textual (lexical choices, modalities, representational strategies), discursive (production, distribution, consumption of discourse), and sociocultural (patriarchal context, racism, militarism). The results showed five main thematic categories: epistemic discrimination (18 emergences), resistance through literacy (24), collective solidarity (21), institutional exclusion (15), and agency and leadership (27). The identified typologies of feminist discourse include liberal, socialist, and radical currents, which are integrated into the narrative. From a psychological perspective, the findings reveal the psychological impact of persistent marginalization on the formation of women's identities, as well as the role of collective solidarity as a psychological resource that restores and empowers. This study concludes that education in the novel is not limited to formal instruction, but rather includes experiential and communal learning that enables women to develop critical awareness, build psychological resilience, and collectively challenge patriarchal and racial structures toward structural transformation and epistemic justice. Keywords: african american literature, empowerment, feminist critical discourse analysis, intersectionality, psychology, resistance, women's education